2012
DOI: 10.1590/s0100-40422012001000018
|View full text |Cite
|
Sign up to set email alerts
|

Especiação de cobre e zinco em urina: importância dos metais em doenças neurodegenerativas

Abstract: Recebido em 5/3/12; aceito em 19/6/12; publicado na web em 31/8/12 SPECIATION OF COPPER AND ZINC IN URINE -IMPORTANCE OF METALS IN NEURODEGENERATIVE DISEASES.Metals such as copper and zinc are essential for the development and maintenance of numerous enzymatic activities, mitochondrial functions, neurotransmission, and also for memorization and learning. However, disruption in their homeostasis can cause neurodegenerative disorders such as the Alzheimer and Parkinson diseases. In this work, the speciation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
2
0
1
Order By: Relevance
“…[ 16,18 ] Similarly, the level of Zn 2+ is observed to be two‐ to threefold higher in the Aβ of AD patient's brain than that of the healthy control. [ 19 ] Moreover, previous studies have demonstrated that the imbalance of Cu 2+ could damage the dopaminergic neurons accompanied by the abnormal aggregation of α‐synuclein, [ 20 ] which is a key clue to the lesions in PD.…”
Section: Ion Dyshomeostasis In Nddsmentioning
confidence: 99%
“…[ 16,18 ] Similarly, the level of Zn 2+ is observed to be two‐ to threefold higher in the Aβ of AD patient's brain than that of the healthy control. [ 19 ] Moreover, previous studies have demonstrated that the imbalance of Cu 2+ could damage the dopaminergic neurons accompanied by the abnormal aggregation of α‐synuclein, [ 20 ] which is a key clue to the lesions in PD.…”
Section: Ion Dyshomeostasis In Nddsmentioning
confidence: 99%
“…These data show the importance of metal determination in biological samples related to AD, as well as the use of chelation therapies (Leal et al, 2012). For example, the work of the research group led by A. Bush suggests that the exacerbated deregulation of metal homeostasis would not only lead to aggregation and deposition of Aβ, but that in parallel would lead to the accumulation of iron within the neurons, causing oxidative damage and neurodegeneration (Bush et al, 1994;Barnham et al, 2004;Friedlich et al, 2004;Adlard et al, 2010;Adlard et al, 2011;Sensi et al, 2011;Bush, 2013).…”
Section: Metals Involved In Admentioning
confidence: 99%
“…Os métodos eletroquímicos apresentam uma vantagem sobre a maioria das outras técnicas analíticas, uma vez que provocam uma perturbação mínima dos sistemas durante a medição. A voltametria de redissolução, que combina uma etapa de préconcentração com uma etapa de medição eletroquímica dos analitos acumulados, é uma ferramenta poderosa para o monitoramento de metais em quantidades traço em diversas amostras [1],[6],[37].…”
unclassified